PENGEMBANGAN EKONOMI KREATIF BERBASIS POTENSI LOKAL UNTUK MEMPERKUAT KETAHANAN EKONOMI DAERAH : Strategi Pengembangan Ekonomi Kreatif Berbasis Kearifan Lokal dalam Memperkuat Ketahanan Ekonomi Daerah - Masitha, Anisa Dewi (PT. Tangrasula Tekno Kreatif, 2025)
The creative economy is now recognized as one of the main drivers of sustainable economic development and plays a significant role in strengthening national economic resilience. Based on the creative economy approach, economic resilience can be achieved through the implementation of diversification and innovation principles. The creative economy promotes the expansion of economic sectors by developing fields such as art, design, music, film, and technology, thereby enabling the formation of a more adaptive economic structure. This diversification offers protection against fluctuations in certain sectors, as other sectors can compensate for the impact. In addition, the creative economy contributes to enhancing economic resilience through job creation, new entrepreneurial opportunities, and the strengthening of cultural diversity and social integration. Within the framework of Michael Porter’s strategic theory, the development of this sector can be directed through three main strategies: low-cost strategy, differentiation strategy, and focus strategy. This study aims to formulate policy recommendations for the government regarding strategies for developing the creative economy to support economic resilience in Indonesia. By employing a literature review method, this research explores the real and specific conditions of the creative economy sector based on available empirical references. The findings indicate that systematically and integratively developed creative economy strategies have positive prospects for reinforcing economic resilience. Therefore, it is recommended that the government pay attention to supportive regulatory and policy frameworks, enhanced access to funding and investment, capacity building through education and training, optimization of promotion and marketing, the development of collaboration and partnership networks, as well as adequate infrastructure provision.